Students’ Learning Style of an Elite Professional College - Singh, Chandra B. P. (INDIAN EDUCATIONAL REVIEW, 2019)
The study was conducted on a sample of students (n=277) enrolled in an elite professional institute to identify dynamics of variation in learning styles. Classroom ecology and teaching styles were regressed on the learning styles. The results indicated that students opted for deep learning style when teachers adopted student-centric approach to teaching in a challenging classroom situation. They had more choice for strategic learning style in case of teacher-centric mode of teaching followed by challenging classroom. The demand of surface learning style came to the notice when teachers adopted teacher-centric approach to teaching. A significant difference between general and SC students was noted on deep learning style. The remaining learning styles did not make any difference across category. The study discussed variation in learning styles in the light of functioning and capabilities.